Implications of Sea Toll Programs to National Development Economy: Reinterpretation of Marine Verses In Al-Quran - Witro, Doli; Yanti , Betria Zarpina (El-Qish: Journal of Islamic Economics, 2021)
Indonesia, as an archipelago with a coastline of 81,000 km, is a coastal and marine area that has a variety of vast and diverse resources. With the unique potential and economic value of development, coastal areas are also faced with a high threat, so special handling is needed so that this region can be managed sustainably. Economic development in this framework is realized through the sea toll program. This article will aim to discuss how the sea toll program has an impact on the national development economy and the reinterpretation of marine verses in Al-Quran. This study uses qualitative research methods that are literature research. The sources of data in this study were sourced from books, journals, scientific articles, research reports, laws, and internet websites related to the sea toll program. After all, data have been collected, the data are analyzed by data analysis methods, namely data reduction, data presentation, and conclusion drawing. Findings. The results showed that the use of marine wealth by humans is justified in Al-Quran even it is recommended for the benefit of humans. On the other hand, the development of defense forces requires strong economic capabilities as a form of an effort to realize Indonesia’s ideals as a world maritime nation. Indonesia’s maritime potential can create a dominant economic development power for the Indonesian state to face global or international competition.